Предмет: Алгебра, автор: Гюля11

Помогите, пожалуйста, с решением

Приложения:

Ответы

Автор ответа: m11m
0
1) y=2*3^{x}-3x^{-3}+5x+x^{- frac{1}{2} }-3lnx+ frac{1}{3}x- sqrt{3} \ 
 \ 
y' =2*3^{x}*ln3-3*(-3)x^{-4}+5- frac{1}{2}x^{- frac{3}{2} }-3* frac{1}{x}+ frac{1}{3}= \ 
=2*3^{x}*ln3+ frac{9}{x^4}- frac{1}{x sqrt{x} } - frac{3}{x}+5 frac{1}{3}     \ 
 \ 
2) y=cosx*(2x^5+1) \ 
 \ 
y'=-sinx(2x^5+1)+10x^4cosx \

3) y'= frac{3 sqrt{5+6x} -(3x+7)* frac{6}{2 sqrt{5+6x} } }{5+6x}= \ 
= frac{3 sqrt{5+6x}- frac{3(3x+7)}{ sqrt{5+6x} }  }{5+6x}= \ 
= frac{3(5+6x)-9x-21}{( sqrt{5+6x} )(5+6x)}= \ 
= frac{15+18x-9x-21}{( sqrt{5+6x} )(5+6x)}= \ 
= frac{9x-6}{( sqrt{5+6x} )(5+6x)}
Похожие вопросы